Crystal structures, thermogravimetric and magnetic properties of four organodiamine templated vanadium oxide frameworks: Influences of diaminoalkane templates - Thapanon Settheeworrarit (2018)
A series of four diaminoalkane templated vanadium oxide polymeric frameworks, [V2IVO8V2VO2](C2H10N2), [V2IVO8V2VO2](C3H12N2), [V4IVO10V2VO4](C4H14N2) and [V4IVO10V2VO4](C5H16N2), have been successfully prepared under hydrothermal conditions. The crystal structures are fully characterized revealing layered structures composed of common inorganic building units, namely VIVO5 square pyramids and VVO4 tetrahedra. The layer registries are different depending on the molecular structure of the diaminoalkanes, and can be accounted for by the organic-inorganic interface interactions. The analysis of hydrogen bonds indicates their important role in directing two- and three-dimensional structural architectures. The influences of different diaminoalkanes are also apparent in both thermogravimetric and complex magnetic behaviors, and are discussed in details. © 2007 Springer Science+Business Media, LLC.